Advertising literacy to empower the young media consumers in India: a critical exploration of the advertised mind. Issue 3 (2nd October 2017) - Trehan, Kulveen
Abstract : This paper explores the levels of television advertising literacy amongst the young media consumers in Urban India. Through group discussions with children around 12 years, it was found that while young audiences love to watch and talk ads, their abilities to read between the lines or grasp the hidden intent is still limited or illogically driven. Cultivation and cross association of images from across media and onto the real world was visibly evident. The young are circumspect to the guile of ad tactics highlighting the need for advertising literacy to empower the new age consumer, especially against misleading claims and sexual imagery in advertising.